Cigarette smoking and high-risk HPV DNA as predisposing factors for high-grade cervical intraepithelial neoplasia (CIN) in young Brazilian women - Roteli-Martins, Cecilia Maria; Panetta, Kazue; Alves, Venancio Avancini Ferreira; Siqueira, Sheila Aparecida Coelho; Syrjänen, Kari Juhani; Derchain, Sophie Françoise Mauricette (Wiley, 1998)
Background. This cross-sectional study was designed to evaluate the role of cigarette smoking and high-risk HPV types as risk factors of CIN 2 and 3 in young, sexually active Brazilian women. Materials and method. A series of 100 consecutive women with abnormal Pap smears were recruited, subjected to colposcopy, punch biopsy, and questionnaire for their social, sexual and reproductive factors. Of these, 77 women between 20 and 35 years of age (median 26.5 years) with biopsy-confirmed CIN 1 or CIN 2 and 3, were enrolled in this study. Representative samples from the exocervix and endocervix were obtained for HPV testing with the Hybrid Capture HPV-DNA assay, including the probes for the oncogenic HPV types (16, 18, 31, 33, 35, 45, 51, 52 and 56). Results. The overall rate of CIN 2 and 3 was 23/77 (29.8%). The women with CIN 1, 2 and 3 did not differ from each other with regard to their age, race, schooling, marital status, life-time number of sexual partners, age at first intercourse, use of oral contraceptives, or parity. However, current cigarette smoking was strongly associated with CIN 2 and 3 (p < 0,001), and among smokers, the risk of high-grade CIN increased in parallel with the time of exposure (years of smoking) p = 0.07), HPV-DNA of the oncogenic types was detected in 43 (56%) women, the risk of being HPV DNA-positive was significantly higher in CIN 2 and 3 as compared with CIN 1 (p = 0.037). Importantly, the prevalence of high-risk HPV types was significantly higher in cigarette smokers than in non-smokers (p = 0.046). Conclusions. The results indicate that the severity of CIN lesions was clearly related to two fundamental risk factors: 1) high-risk HPV types, and 2) current cigarette smoking. These two risk factors were closely interrelated in that the high-risk HPV types were significantly more frequent in current smokers than in non-smokers, suggesting the possibility of a synergistic action between these two risk factors in cervical carcinogenesis.
Keywords: Cervical intraepithelial neoplasia (CIN); Human papilloma virus (HPV); Risk factor; Smoking; oral contraceptive agent; virus dna; adult; brazil; cancer risk; cancer susceptibility; cigarette smoking; colposcopy; education; female; human; human cell; human tissue; major clinical study; marriage; papanicolaou test; parity; priority journal; punch biopsy; questionnaire; risk factor; sexual behavior; sexual intercourse; social behavior; uterine cervix carcinoma in situ; uterine endocervix; wart virus; Adult; Biopsy; Brazil; Cervical Intraepithelial Neoplasia; Cross-Sectional Studies; DNA, Viral; Female; Humans; Papillomaviridae; Papillomavirus Infections; Prevalence; Questionnaires; Risk Factors; Sexual Behavior; Tumor Virus Infections; Uterine Cervical Neoplasms; Women's Health